Learning from the community: iterative co-production of a programme to support the development of attention, regulation and thinking skills in toddlers at elevated likelihood of autism or ADHD - Alexandra Hendry; Victoria Hulks; Shona Murphy; Holly Radford; Sally Smith; Tony Charman; Sandra Mathers; Sinead Rhodes; Gaia Scerif (Research Involvement and Engagement)
Abstract Programmes designed to support children with known, or increased likelihood of, autism or ADHD often focus on reducing behaviours central to a clinical diagnosis. However, supporting children to pursue their own goals and cope with everyday life through fostering executive function (EF) development, without enforcing neuro-normative assumptions, may be more acceptable to neurodivergent people, and more beneficial. The co-production process for this neurodiversity-affirming programme involved: Review of research priorities identified during published public-and-clinician consultations; iterative programme development through two pilot rounds with a general community sample; and consultation with stakeholders (parents with a connection to autism or ADHD, alongside early years specialists, psychologists and therapists) to check acceptability of the proposal, and refine the logic model and materials. The logic model for the resultant programme—Supporting Toddlers with a connection to autism or ADHD to develop strong Attention, Regulation and Thinking skills (START)—involves three mechanisms of change: The child has appropriate play-based opportunities to practise EF skills; Parenting behaviours linked to strong EFs are encouraged; Parents are empowered to improve environmental-fit for their child so that EF stressors are reduced.